PENERAPAN IFRS DALAM PRAKTIK MANAJEMEN LABA PADA BANK PEMERINTAHAN INDONESIA - Nurshadrina Kartika Sari; Edi Turjono; Nanda Widaninggar (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2017)
Banking sector must use accountability for report their financial statement, because external and internal users use it to evaluate the condition of the company. In other side if banks do earnings management practices it will not support for these purpose. IFRS (International Financial Reporting Standards) as the global financialstandards that more accountable and transparance. This standard can push down the earnings management practice do by management. This research aims to obtain empirical evidence of IFRS implementation in earnings management practice, especially in Indonesia Government Banks during the period before and after using IFRS (2008-2015). The method of this research is using t-test by comparing data in 2008 to 2015. The result of this study indicates that there are differences in earnings management practice by management after implementation of IFRS. The contribution of this research is to get the empirical evidence related to the application of financial reporting standar based on IFRS, and producing transparency and accountable of the financial reports and decline in earnings management behavior.Keyword : Earnings Management, IFRS, Loan Loss Provision, Government Bank.